An empirical investigation of suicide schemas in individuals with Posttraumatic Stress Disorder. Issue 2 (30th June 2015) - Panagioti, Maria; Gooding, Patricia A.; Pratt, Daniel; Tarrier, Nicholas
Abstract: Posttraumatic Stress Disorder (PTSD) has been strongly associated with suicidality. Despite the growing evidence suggesting that suicidality is heightened by the presence of an elaborated suicide schema, investigations of suicide schemas are sparse. Using novel methodologies, this study aimed to compare the suicide schema of PTSD individuals with and without suicidal ideation in the past year. Fifty-six participants with a diagnosis of PTSD (confirmed via the Clinician Administered PTSD Scale) completed questionnaires to assess suicidality, depressive severity and hopelessness. A series of direct and indirect cognitive tasks were used to assess suicide schemas. The pathfinder technique was employed to construct graphical representations of the groups׳ suicide schemas. The suicidal group reported significantly more severe PTSD symptoms, depressive symptoms, hopelessness and suicidality. The suicide schema of the suicidal group was significantly more extensive compared to the non-suicidal group even after taking into account in the analyses group differences in clinical measures. Moreover, the suicide schemas of the two groups were qualitatively distinct from each other. These findings provide support for contemporary theories of suicide which view suicide schemas as an important indicator of suicide risk. The investigation of schema constructs opens a new avenue of research for understanding suicide. Highlights: A novel methodology for assessing suicide schemas in PTSD was tested. Responses at suicide schema tasks differentiated suicidal from non-suicidal group. Between-group differences were maintained whilst controlling for clinical measures. Findings support contemporary theories of suicide.